2010
DOI: 10.3109/01676830903278191
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Presentations of Orbital Echinococcosis: A Report of Two Cases and Review of the Literature

Abstract: Clinical findings and imaging can help in the preoperative diagnosis of patients with orbital echinococcosis. Knowledge of the nature of cystic orbital lesions is important in preventing complications. Alveolar cysts are more invasive than hydatid cysts and their treatment is more complicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
9
0
9
Order By: Relevance
“…Rajabi et al (2013) reported orbital hydatid cysts with diverse localities in extraconal, medial rectus, intraconal space, lacrimal gland, and intraosseous of the orbital wall (14). Bagheri et al (2010) showed two different presentations of orbital echinococcosis due to hydatid and alveolar cysts in Iranian patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Rajabi et al (2013) reported orbital hydatid cysts with diverse localities in extraconal, medial rectus, intraconal space, lacrimal gland, and intraosseous of the orbital wall (14). Bagheri et al (2010) showed two different presentations of orbital echinococcosis due to hydatid and alveolar cysts in Iranian patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…En diversas publicaciones, las lesiones tumorales quísticas de la órbita en niños, de etiología inflamatoria, están asociadas a infecciones parasitarias, siendo la más frecuente la hidatidosis (8) . En nuestro medio, la infección sistémica por hidatidosis en niños es frecuente y ha sido ampliamente reportada en trabajos epidemiológicos.…”
Section: Cruzado-unclassified
“…Orbital involvement is rare, and the most common symptoms in orbital hydatid cyst are slowly progressive unilateral proptosis, with or without pain, visual deterioration with or without optic disc edema, periorbital pain, headache, and disturbance in ocular mobility 263265. Ultrasonography, computed tomography, and magnetic resonance imaging are diagnostic imaging techniques.…”
Section: Parasitic Optic Neuropathiesmentioning
confidence: 99%
“…Ultrasonography, computed tomography, and magnetic resonance imaging are diagnostic imaging techniques. The condition may be treated with albendazole or surgical removal of cysts 263265…”
Section: Parasitic Optic Neuropathiesmentioning
confidence: 99%